How to choose healthier urban biking routes: CO as a proxy of traffic pollution - Bertrand, Lidwina (2020)
According to the World Health Organization (WHO) air pollution in urban areas, mainly associated with inhalation of gaseous pollutants and particulate matter emitted from motor vehicles, is responsible for one million deaths per year. Carbon monoxide (CO) from the incomplete combustion of fuel is known to bind with hemoglobin, decreasing the blood oxygen-delivery and inducing tissues hypoxia; being more pronounced under conditions of stress like physical activity. The present study demonstrates the usefulness of a compact CO sensor (Alphasense CO-B4) mounted on a bicycle to evaluate atmospheric levels of CO associated with urban microenvironments within a growing Australian city (Brisbane). Urban bike pathways show pronounced and significant variations in air quality according to the surrounding microenvironment and the time of day. The inhaled dose in real time and the CO total dose over each trip were valuable for estimating the air quality of the route, and identifed how the health benefits of riding a bicycle could be partially offset by poor air quality depending on where and when a cycle route is taken in the inner-city. Finally, environmental conditions, such as wind speed, were found to significantly affected atmospheric CO concentrations, at least during the study period. The present work provides information regarding commuters' exposure to atmospheric pollutants, necessary for modifying the population's (including cyclists) perception of pollution in the urban environment, providing people with the opportunity to choose a healthier route.